The TFAP2A–IRF6–GRHL3 genetic pathway is conserved in neurulation. (25th January 2019) - Kousa, Youssef A; Zhu, Huiping; Fakhouri, Walid D; Lei, Yunping; Kinoshita, Akira; Roushangar, Raeuf R; Patel, Nicole K; Agopian, A J; Yang, Wei; Leslie, Elizabeth J; Busch, Tamara D; Mansour, Tamer A; et al.
Abstract: Mutations in IRF6, TFAP2A and GRHL3 cause orofacial clefting syndromes in humans. However, Tfap2a and Grhl3 are also required for neurulation in mice. Here, we found that homeostasis of Irf6 is also required for development of the neural tube and associated structures. Over-expression of Irf6 caused exencephaly, a rostral neural tube defect, through suppression of Tfap2a and Grhl3 expression. Conversely, loss of Irf6 function caused a curly tail and coincided with a reduction of Tfap2a and Grhl3 expression in tail tissues. To test whether Irf6 function in neurulation was conserved, we sequenced samples obtained from human cases of spina bifida and anencephaly. We found two likely disease-causing variants in two samples from patients with spina bifida. Overall, these data suggest that the Tfap2a-Irf6-Grhl3 genetic pathway is shared by two embryologically distinct morphogenetic events that previously were considered independent during mammalian development. In addition, these data suggest new candidates to delineate the genetic architecture of neural tube defects and new therapeutic targets to prevent this common birth defect.